2023
DOI: 10.1158/2159-8290.c.6568429.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from The DNA Damage Response and Inflammation in Cancer

Abstract: <div>Abstract<p>Genomic stability in normal cells is crucial to avoid oncogenesis. Accordingly, multiple components of the DNA damage response (DDR) operate as bona fide tumor suppressor proteins by preserving genomic stability, eliciting the demise of cells with unrepairable DNA lesions, and engaging cell-extrinsic oncosuppression via immunosurveillance. That said, DDR sig­naling can also favor tumor progression and resistance to therapy. Indeed, DDR signaling in cancer cells has been consistently… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The DNA damage response plays a pivotal role in recruiting and activating immune cells by upregulating the expression of immunostimulatory signals. While the DNA damage response contributes to maintaining the microenvironment and organismal homeostasis, it has been suggested that it might also play a role in tumorigenesis and progression [ 163 ]. Recent studies have shown that DHA triggers cellular iron death, resulting in the production of reactive oxygen species, which in turn induces endoplasmic reticulum stress and DNA damage.…”
Section: Association Of Tams With Lung Cancer Treatmentmentioning
confidence: 99%
“…The DNA damage response plays a pivotal role in recruiting and activating immune cells by upregulating the expression of immunostimulatory signals. While the DNA damage response contributes to maintaining the microenvironment and organismal homeostasis, it has been suggested that it might also play a role in tumorigenesis and progression [ 163 ]. Recent studies have shown that DHA triggers cellular iron death, resulting in the production of reactive oxygen species, which in turn induces endoplasmic reticulum stress and DNA damage.…”
Section: Association Of Tams With Lung Cancer Treatmentmentioning
confidence: 99%